Diet of the black sea urchin Echinometra lucunter (Echinometra: Echinoidea) in the northeast of Venezuela. - Reyes-Luján, Jeny; Barrios, Jorge; Arrieche, Dwight; Zapata-Vívenes, Edgar; Salgado, Wil; Lodeiros, César (Revista de Biología Tropical, 2015)
Echinometra lucunter is relatively abundant in the Venezuela coast, however no details are known about its diet. We compare the stomach contents and repletion index of E. lucunter with macroalgae available in their environment (June 2010-August) and the nutrient cycle at the Golfo de Cariaco. Seventy-one species of macroalgae were identified: Rhodophyta (45), Heterokontophyta (11) and Chlorophyta (15). The mean testa diameter was 41.04 ± 6.60 mm. The food preferences included filamentous, siphonal and calcaeous macroalgae; main food items were the filamentous macroalgae Sphacelaria sp. and Herposiphonia sp., and foliose Dictyota sp., including invertebrates such as sponges, bivalves and barnacle crustaceans. The repletion index was 0.8 - 6.0 % (2.6 ± 1.21 %), maximum values were associated to primary productivity cycle, i.e. December 2010 (6.0 ± 2.21 %), April (4.3 ± 0.34 %), June 2011 (4.0 ± 1.79 %). Food preferences could be associated to the upwelling season and productivity cycle.